KONFLIK ELIT POLITIK DALAM PEMILIHAN UMUM GUBERNUR DAN WAKIL GUBERNUR PROVINSI MALUKU UTARA TAHUN 2007 - Husen, Muhammad Rahmi (Universitas Sam Ratulangi, 2016)
Conflict elections of regional heads the governor and vice governor North Maluku involving the supporters so as to campaign vying for power as the governor and vice governor North Maluku. Conflict take place due to the presence of the same interests both of stronghold to lead North Maluku. Based on field findings show, that: first, the conflict started seen since registration stage candidates, not fulfilling the applicable provisions namely 15% to votes support and seats support. Second, stage campaign period, conflict can also be seen start hardened on the of this phase because third candidate couple and team the success of protest against the schedule some of which day has fallen during Ramadan and Eid, whereas when the socialization of future phases of this campaign is well accepted by all parties. Third, calculation stage and recapitulation the ballot, in this phase conflict is more open and prolonged because caused the political elite prefer the interests of each as to be almost no space negotiations to conflict resolution. The political elite just focused on the results and ignore the process so that allowed various ways of winning candidates which results in conflict. Fifth, conflict general election governor and the vice governor of North Maluku in 2007 it ended after the issuance of the decisions law for the winner by Mahkamah Agung (MA) and the rejection dispute authority between agencies requested by KPUD provincial North Maluku in Mahkamah Konstitusi (MK). Conflict general election the governor and vice governor this was caused by as the game the political elite who became patron from the supporting so that conflict. For it, for elite that will hold the power, to prevent ways violence in seized power. Keywords: political elite, supporters, conflict